Annually Recurring Erythema Annulare Centrifugum: A New Case Series with Review of the Literature - Martina Maurelli; Paolo Gisondi; Chiara Colato; Giampiero Girolomoni (Karger Publishers, 2021)
Annually recurring erythema annulare centrifugum (AR-EAC) is a rare variant, characterized by typical annular plaques recurring in the same period of the year. We describe 5 new cases and present a review of the literature. Patients were 3 females and 2 males with an age range of 25-55 years. Multiple annular plaques were located at the thighs in 4 patients and the neck in one patient. In 1 patient, a single lesion was present. Plaques were recurring in summer in 3 cases; in 1 case, in spring; and another patient, in winter since 3-4 years. Lesions were self-healing in few days or weeks. Histologically, the epidermis presented mild acanthosis with patchy spongiosis, slight parakeratosis, and mild exocytosis. There was a perivascular lympho-histiocytic infiltrate of variable intensity in the superficial dermis, with occasional eosinophils. In 1 case, the inflammatory infiltrate reached the deep dermis. Mucin deposition was absent. Phenotyping studies in 1 case revealed a predominance of T cells, with a small B-cell component. Moreover, a moderate number of CD123+ plasmacytoid dendritic cells and CD1a+ dendritic cells were noted. Fourteen cases of AR-EAC have been published previously. Collectively, patients' age ranged from 16 to 83 years, with a mean age of 47 years and a disease duration of 1-30 years. Lesions affected more frequently extremities and recurred most commonly in summer. Patients were all in good general health. Topical corticosteroids were the mainstay of treatment. AR-EAC is a benign disorder, the nature of which remains enigmatic.